Brand Community and Its Effect on Apple Community Members - Tejuja, Roshni Arun (2011)
Research on brand communities have only been restricted to brand and consumer. Only little research has been conducted on brand communities and its members. Moreover the effects of brand communities on its members have not yet been researched. This paper aims at gaining the members perspective about the brand and their attributed or attitude towards it. The paper will focus on various components such as loyalty, trust, consumer empowerment, elements of brand community, pricing, linking towards the brand. These aspects will be elaborated and analysed. These components will be established using qualitative method. Semi structured interviews of 12 Apple brand community members will be taken and further analysed.